2012
DOI: 10.1523/jneurosci.0680-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Improved Sensorimotor Performance via Stochastic Resonance

Abstract: Several studies about noise-enhanced balance control in humans support the hypothesis that stochastic resonance can enhance the detection and transmission in sensorimotor system during a motor task. The purpose of the present study was to extend these findings in a simpler and controlled task. We explored whether a particular level of a mechanical Gaussian noise (0 -15 Hz) applied on the index finger can improve the performance during compensation for a static force generated by a manipulandum. The finger posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
74
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(105 citation statements)
references
References 60 publications
13
74
4
Order By: Relevance
“…As suggested by Mendez-Balbuena et al (2012), an explanation of the improved performance in our task during optimal noise is related to an enhanced neuronal synchronization at spinal, cortical, and corticospinal level.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…As suggested by Mendez-Balbuena et al (2012), an explanation of the improved performance in our task during optimal noise is related to an enhanced neuronal synchronization at spinal, cortical, and corticospinal level.…”
Section: Discussionsupporting
confidence: 60%
“…Recently, we have demonstrated that the EEG-EMG coherence was related to the precision of performance in a visuomotor task (Kristeva et al, 2007; Mendez-Balbuena et al, 2012). The improved precision in the pseudo-isometric compensation of a SF correlated with higher beta-range cortical motor SP and higher beta-range CMC.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been demonstrated that vibration stimuli of frequencies up to 15 Hz may lead to enhanced stability in sensorimotor tasks (Mendez-Balbuena et al, 2012). It is not far to speculate that neuronal facilitation as demonstrated in the present study in the context of train stimuli may contribute to such findings.…”
Section: Discussionsupporting
confidence: 68%
“…An example of sensory stochastic resonance with wide-scale clinical applications is in tactile sensing and motor control [65]. Somatosensory function declines in people as we age, and further such changes are associated with diminished motor performance.…”
Section: Stochastic Resonance In Biological Systemsmentioning
confidence: 99%